The Effect of Just in time (JIT) and Supply Chain Management on Company Performance at Seafood Restaurants in Ambon City - Fransiska N Ralahallo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of good performance is the main thing that becomes the success of a company or organization. This study aimed to determine the effect of just in time and supply chain management on company performance at seafood restaurants in Ambon city. The population in this study is a restaurant in Ambon city that gets fish supply. The data used in this study were obtained from the results of filling out the questionnaire, for 35 respondents at 20 seafood restaurants in Ambon city. Data collection techniques in this study used a questionnaire. The instrument testing was carried out before the analysis including the validity test, the reliability test, the multicollinearity test, the heteroscedasticity test, and the data normality test. Data analysis used to test the hypothesis was multiple linear regression analysis techniques. The results showed that just in time had a positive and significant effect on company performance while supply chain management had a positive and significant effect on company performance.